2003
DOI: 10.1093/nar/gkg803
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of DNA duplex containing an N-(2-deoxy- -D-erythro-pentofuranosyl) formamide frameshift by NMR and restrained molecular dynamics

Abstract: The presence of an N-(2-deoxy-beta-D-erythro-pentofuranosyl) formamide (F) residue, a ring fragmentation product of thymine, in a frameshift context in the sequence 5'-d-(AGGACCACG)*d(CGTGGFTCCT) has been studied by 1H and 31P nuclear magnetic resonance (NMR) and molecular dynamics. Two-dimensional NMR studies show that the formamide residue, whether the cis or trans isomer, is rotated out of the helix and that the bases on either side of the formamide residue in the sequence, G14 and T16, are stacked over eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…During this simulation, the THF abasic site moves spontaneously from an intrahelical position to an extrahelical position and remains outside during the remainder of calculations. The phosphate backbone forms a right-handed loop ( 38 ) leading the THF residue to move into the minor groove, leaving it completely exposed to the solvent. On the contrary, the cytosine facing the THF site remains intrahelical during the entire simulation ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%
“…During this simulation, the THF abasic site moves spontaneously from an intrahelical position to an extrahelical position and remains outside during the remainder of calculations. The phosphate backbone forms a right-handed loop ( 38 ) leading the THF residue to move into the minor groove, leaving it completely exposed to the solvent. On the contrary, the cytosine facing the THF site remains intrahelical during the entire simulation ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of these compounds in some reaction steps can be one of the reasons for many preferential interactions that take place in the living matter. [1] Several hydrogen-bonded formamide (FA) complexes have been investigated in our laboratory and the results are important for a better understanding on the nature of the hydrogen bond in systems exhibiting the peptide type of bonding and DNA structures. [2] In those works, FA essentially acts as a Lewis acid where its N-H site causes wavenumber shifts of the characteristics bands of acetonitrile (ACN), [3] dimethylsulfoxide (DMSO), [4] tetrahydrofuran (THF), [5] and dioxane (DX).…”
Section: Introductionmentioning
confidence: 99%
“…So far, all spectroscopic studies on hydrogen-bonded Py complexes have used the Raman technique as a tool and the bands between 990 and 1030 cm −1 (ring-stretching modes of Py) as markers for monitoring changes in the local environment of this molecule. [9 -15] In this paper, we report FT-Raman and FTIR studies of FA and Py mixtures at different compositions and the experiments are designed to (1) show for the first time another spectral region of Py which is strongly perturbed by coordination with hydrogen and (2) determine the stoichiometry of the FA : Py adduct as being an initial step for a future study on the FA adducts' stability. Owing to its good performance, density functional theory (DFT) was also employed in this investigation to support the experimental evidences, and a good agreement was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…3 -5 On the other hand, there is no work in the literature on intermolecular interactions involving these two molecules. Only a recent study performed by Maufrais et al 6 has shown the existence of an N-(2-deoxy-ˇ-D-erythropentofuranosyl) FA residue which was obtained from the thymine ring fragmentation. Such residue corresponds to a chemical modification induced in cellular DNA exposed to the action of an ionizing radiation and it plays an important role in biological processes such as mutagenesis, carcinogenesis and cell lethality.…”
Section: Introductionmentioning
confidence: 99%